Natural Disaster and Intangible Heritage: Beyond the Horizon - Maharjan, Monalisa (2016)
When 7.8-magnitude earthquake struck Nepal in 2015, many monuments, temples and houses turned into rubbles killing more than 8,000 people and injuring above 21,000. This unfortunate and tragic natural disaster brought international attention to Nepal. But in this time of despair and pain there was a sign of hope that should be acknowledged well, the spirit of community facing the disaster. This paper is about the indigenous community of Kathmandu on how they organized an important traditional festival just four months after the disaster when most the people were still living in the makeshifts, along with the smaller aftershock continuing almost everyday. In the country like Nepal with numerous intangible heritages, which is, still living is not taken seriously by the concerned authorities and mostly been neglected. It is the indigenous community who has been carrying out those heritages, as they are inseparable aspect of the social life. With this paper it tries look at the community involvement and intangible heritage of Kathmandu Valley, which is a part of my PhD research thesis.